ANALYSIS OF FACTORS AFFECTING THE INTENTION TO PURCHASE ELECTRIC VEHICLES: A SYSTEMATIC LITERATURE REVIEW (SLR) - Putri, Riri Ramadhani (Departemen Teknik Industri, Fakultas Teknik, Universitas Diponegoro, 2024)
Electric vehicles are a type of vehicle that is driven by an electric motor powered by a battery. Electric vehicles are gaining popularity worldwide due to increasing environmental awareness and various benefits such as reduced dependence on fossil fuels and being considered an efficient and sustainable mode of transportation. This research presents a comprehensive overview and bibliometric analysis of published studies related to consumer adoption/purchase intentions of electric vehicles (EVs) from 2014 to 2024. The Scopus database was used to extract the papers as it is considered the largest database of peer-reviewed academic publications colleagues. VOS Viewer software was used for bibliometric analysis of networks between authors, institutions, countries, publications, journals, and keyword occurrences. The research was conducted on March 23, 2024, which resulted in a total of 154 documents after exclusion using selected keywords. These findings show a sizable increase in publications regarding intentions to adopt electric vehicles over the past six years. China is the world leader in this research field, providing the maximum number of papers. Sustainability Switzerland Journal stands out as the most productive journal with the most publications. This analysis will help academics better understand historical trends, current challenges, and future research topics in the area of electric vehicle adoption/purchase intentions.